Achieving Both High Selectivity and Current Density for CO2 Reduction to Formate on Nanoporous Tin Foam Electrocatalysts. Issue 8 (9th June 2016) - Du, Dongwei; Lan, Rong; Humphreys, John; Sengodan, Sivaprakash; Xie, Kui; Wang, Huanting; Tao , Shanwen
Abstract: Currently, low catalytic activity, selectivity and stability are the biggest challenges which restrict the large scale applications of CO2 electrochemical reduction. Formic acid, one of the highest value‐added products from electrochemical reduction of CO2, has gathered much interest. Here, we develop nanoporous tin foam catalysts which exhibit significantly high selectivity and faster production rate to formate. In a 0.1 M NaHCO3 solution, the maximum Faradaic efficiency for formate production can reach above 90 % with a current density over 23 mA cm −2, which are among the highest reported to date under ambient conditions. The improved production rate can be attributed to the high surface area and porous structure. Moreover, the electrocatalysts are quite stable, namely, the Faradaic efficiency remains unchanged during 16 hour electrolysis. Abstract : Nanoporous tin foam catalyst composed of small tin dendrites was prepared via an electrodeposition method. The catalyst was applied in CO2 electroreduction. In NaHCO3 solution, it exhibited significantly high selectivity and faster production rate for CO2 to formate with good stability.